Peningkatan Pemahaman Siswa-siswi dalam Penanganan dan Perawatan Kucing yang Efektif Mencegah Infeksi Toxoplasmosis: Improving Students Understanding on Effective Cat Handling and Caring to Prevent Toxoplasmosis Infection - Augustina, Indria; Toemon, Agnes Immanuela; Turnip, Oktaviani Naulita (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Approximately 2 billion people, equivalent to half of the world's population, suffer from toxoplasmosis. Toxoplasmosis is a disease caused by the parasite Toxoplasma gondii that infects cats as its definitive host. Not only cats, T. gondii can also infect animals such as chickens, cows, goats, pigs, and sheep that act as intermediate hosts, including humans. Both feral and pet cats have the potential to be infected with T. gondii. Toxoplasmosis infection in humans can cause various disorders and diseases such as obertus, encephalomyelitis, chorioretinitis, hydrocephalus in newborns, and infertility in women. This activity aims to improve the participants' understanding in terms of pet cat care and effective handling of stray cats in preventing toxoplasmosis infection. The stages of activities carried out began with pretest, socialisation, discussion, posttest, and documentation of activities. The results of this activity showed an increase in participants' knowledge and understanding related to toxoplasmosis, which can be seen from the increase in post-test scores compared to the pre-test scores.